Incidence of urinary ketosis and the effect of carbohydrate drink supplementation during fasting for elective caesarean section: Audit. Issue 11 (November 2022) - Bellwood, Hannah; Rozdarz, Kellie M; Riordan, John
Elective lower segment caesarean section patients are routinely instructed to fast from food for 6h before surgery, with clear fluids up until 2h before surgery. We conducted an audit examining the true fasting times of mothers undergoing an elective caesarean section and the incidence of urinary ketones before and after introducing a preop carbohydrate drink (Nutricia preOp 400ml) to be administered to all patients at 6am on the day of surgery. We audited 50 patients prior to introducing the preop carbohydrate drink and 54 patients after the introduction of a carbohydrate drink. We found the mean fasting time from last caloric intake was reduced from 13h 35min to 5h 5min after the introduction of a preoperative carbohydrate drink. We found that the incidence of urinary ketones was 40.4% prior to the introduction of a preoperative carbohydrate drink and 38.3% after the introduction of a preop drink (p = 1). If fasting times were limited to under 4h, the incidence of urinary ketones is 10%. Our audit demonstrates that reducing preoperative fasting times is possible and preventing metabolic derangements may be possible, requiring an approach targeted at keeping fasting times to a minimum.